High Dietary Iron Supplement Induces the Nigrostriatal Dopaminergic Neurons Lesion in Transgenic Mice Expressing Mutant A53T Human Alpha-Synuclein - Jia, Fengju; Song, Ning; Wang, Weiwei; Du, Xixun; Chi, Yajing; Jiang, Hong (Frontiers in Aging Neuroscience, 2018)
Both alpha-synuclein aggregation and iron deposits are neuropathological hallmarks of Parkinson's disease (PD). We are particularly interested in whether iron could synergize with alpha-synuclein pathology in vivo, especially in the nigrostriatal system. In the present study, we reported transgenic mice with overexpressing human A53T alpha-synuclein, as well as WT mice with high dietary iron displayed hyperactive motor coordination and impaired colonic motility, compared with those with basal dietary iron. Only A53T mice, but not WT mice with high dietary iron exhibited nigral dopaminergic neuronal loss, lower levels of tyrosine hydroxylase in the substantia nigra (SN) and decreased dopamine contents in the striatum. Although there was no obvious elevation of iron contents in the SN in WT mice with high dietary iron, we observed iron contents in the SN were especially higher than the other brain regions in 12-month aged mice with either high or basal dietary iron. These results suggested high dietary iron supplement could induce nigral dopaminergic neurons lesion in A53T mice, which might be due to the vulnerability of SN to accumulate iron.